Superselective Angioembolisation: A Report of Two Rare Cases of Hemoptysis - Mohammad Sadegh Keshmiri; Babak Sharifkashani; Alireza Serati; Seyed Reza Seyedi; Farah Naghashzadeh; Siroos Salehi; Omid Dehghan (International Journal of Cardiovascular Practice, 2019)
Superselective bronchial embolization is recently performed with a high success rate. The current study aimed at discussing the procedure and reporting two cases underwent embolization in the Masih-Daneshvari Hospital, a large center for this procedure, in Iran.